Occurrence of Teak Defoliator, Hyblaea puera (Hyblaeidae, Lepidoptera) on the Fountain Tree Spathodea campanulata (Bignoniaceae) - Amin, P. W.; Upadhyaya, A. K. (Indian Forester, 1976)
The caterpillars resembling those of teak defoliator, Hyblaea puera, were found feeding on Spatodea in the field. These larvae were identified to be that of Hyblaea puera from the extensive feeding and breeding trials in the laboratory. Teak defoliator larvae were found to prefer Spathodea over teak for food. Spathodea campanulata (Bignoniaceae) is thus a new record of the host plant of teak defoliator.